Στιγμιαία κατασκευή στερεού μείγματος υλικού μέσα από ελεγχόμενη φυσική διαδικασία - Χριστοδούλου, Χριστόδουλος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The purpose of this work was to synthesize the kesterite phase Cu2ZnSnS4 which is of great industrial importance since it can be used as an absorbent in thin film photovoltaic devices. The kesterite phase Cu2ZnSnS4 is usually made by heating the precursor elements or sulfur compounds in a sulfur-containing atmosphere for several hours. These absorbents though reach an energy efficiency of 6.7%. This efficiency and the long processing time are still unsatisfactory. The synthesis of the pure kesterite phase continues to have insurmountable difficulties, as its total isolation cannot be fully achieved. The reason why the pure phase cannot be isolated is related to the processes being implemented as it is evident that there is a lack of understanding and implementation of the thermodynamic equilibrium criteria. In this work we have made use of the most appropriate equilibrium criterion in order to isolate the pure kesterite phase. Also, we interpreted the results of our own experimental work, and discussed as to how to remove the remaining deficiencies of the implemented methodology in the framework of a future attempt to isolate the pure phase without faults.
Keywords: Kesterite; Spontaneity; Equilibrium pressure; Evaporation; Exothermic reaction; Αυθορμητισμός; Πίεση ισορροπίας; Εξάτμιση; Εξωθερμική αντίδραση